Canonization in Islamic Law: A Case Study based on Shāfiʿī Literature - Oberauer, Norbert (Islamic law and society, 2022)
The impact of canonization on the development of law has been the object of considerable discussion in Islamic studies. Drawing on a systematic survey of Shāfiʿī doctrine on commercial partnership as represented in commentaries and abridgements of the 9th to 19th centuries, I argue that canonization made a significant contribution to stabilizing legal doctrine, and thus to conferring an element of rigidity on Shāfiʿī law. At the same time, I argue that this rigidity is specific to commentaries and abridgements, which in turn represent only one of many layers of Islamic legal discourse. The marked conservatism of these texts should be interpreted against the backdrop of the functional differentiation of different genres of legal literature: commentaries and abridgements served to preserve and transmit the inherited doctrinal essence of a school, while other genres helped contextualize this doctrinal tradition within an ever-changing environment of social practices.